Tesla Coil Theoretical Model and its Experimental Verification - Voitkans, Janis; Voitkans, Arnis (Electrical, Control and Communication Engineering, 2014)
In this paper a theoretical model of Tesla coil operation is proposed. Tesla coil is described as a long line with distributed parameters in a single-wire form, where the line voltage is measured across electrically neutral space. By applying the principle of equivalence of single-wire and two-wire schemes an equivalent two-wire scheme can be found for a single-wire scheme and the already known long line theory can be applied to the Tesla coil. A new method of multiple reflections is developed to characterize a signal in a long line. Formulas for calculation of voltage in Tesla coil by coordinate and calculation of resonance frequencies are proposed. The theoretical calculations are verified experimentally. Resonance frequencies of Tesla coil are measured and voltage standing wave characteristics are obtained for different output capacities in the single-wire mode. Wave resistance and phase coefficient of Tesla coil is obtained. Experimental measurements show good compliance with the proposed theory. The formulas obtained in this paper are also usable for a regular two-wire long line with distributed parameters.